Optical Simulations of Organic Solar Cells with PBDB-T:ITIC and PTB7:PC71BM Photoactive Layers - Cuong, Nguyen Duc; Thi Thu Ha, Than; Thi Hoa, Hoang; Thi Thao, Vu; Tuan Canh, Nguyen; Phuong Hoai Nam, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 41 No 1DO - 10.25073/2588-1124/vnumap.4980, 2025)
In this work, we present a comprehensive optical simulation analysis of bulk-heterojunction (BHJ) organic solar cells where PBDB-T:ITIC incorporated with PTB7:PC 71 BM blends served as photoactive layers. The simulations were performed using transfer matrix method implemented through a MATLAB script that is developed by McGehee’s research group at Stanford University. This method involves calculating the optical transmission and reflection at each interface within the multilayer stack, as well as the attenuation of light within each layer. A comparative evaluation was conducted for solar cells employing these active layers in both conventional and inverted configurations, with a focus on key performance metrics including light-harvesting efficiency (LHE), exciton generation rate within the active layer (), and the maximum achievable short-circuit current density (). The obtained results showed that for both types of active layers, the inverted structure achieves a larger  compared to the conventional structure. Additionally, the PBDB-T:ITIC-based absorber outperforms the PTB7:PC 71 BM-based absorber in terms of .